Adulthood Exposure to Lipopolysaccharide Exacerbates the Neurotoxic and Inflammatory Effects of Rotenone in the Substantia Nigra - Huang, Chun; Zhu, Li; Li, Huan; Shi, Fu-Guo; Wang, Guo-Qing; Wei, Yi-Zheng; Liu, Jie; Zhang, Feng (Frontiers in Molecular Neuroscience, 2017)
Parkinson’s disease (PD) is the second most neurodegenerative disorder with a regional decrease of dopamine (DA) neurons in the substantia nigra (SN). The etiology of PD progressive process remains unclear. This study was to investigate the synergistic effects of chronic inflammation of lipopolysaccharide (LPS) and neurotoxicity of rotenone (ROT) on exacerbating DA neuron lesion. Male SD rats received a single intraperitoneal injection of LPS. Seven months later, rats were subcutaneously given ROT five times a week for consecutive 4 weeks. Rat behavior changes were assessed via rotarod and open-field tests. Brain SN was immunostained to evaluate DA neuronal loss and microglia activation. Striatum DA and its metabolites levels were determined by HPLC coupled with electrochemistry. The protein levels of αsynuclein, inflammatory factors and MAPK pathway activation were evaluated by western blotting analysis. Results indicated that no significant difference between the control and LPS alone groups was shown. Compared with ROT alone group, LPS combined with ROT significantly reduced motor activity and induced SN DA neurons loss accompanied by the decreased contents of striatum DA and its metabolites. Furthermore, LPS together with ROT enhanced microglia activation and the increased expressions of αsynuclein and inflammatory factors and also MAPK signaling pathway activation. These findings suggest that chronic inflammation aggravates ROT-induced DA neurotoxicity through microglial activation and inflammatory factors release leading to chronic progressive DA neurodegeneration.